Reoperation for refractory epilepsy in childhood: a second chance for selected patients - Ramantani, Georgia; Strobl, Karl; Stathi, Angeliki; Brandt, Armin; Schubert-Bast, Susanne; Wiegand, Gert; Korinthenberg, Rudolf; Stephani, Ulrich; van Velthoven, Vera; Zentner, Josef; Schulze-Bonhage, Andreas; Bast, Thomas (Neurosurgery, 2013)
Reoperations account for >10% in pediatric epilepsy surgery cohorts, and they are especially relevant in young children with catastrophic epilepsy.To determine surgical outcomes and their predictive factors in reoperations for refractory epilepsy in childhood.We retrospectively analyzed presurgical findings, resections, and outcomes of 23 consecutive children who underwent reoperations from 2000 to 2011.Etiology included cortical dysplasia with/without glioneuronal tumor in 19 patients (83%), sole glioneuronal tumor in 2, and tuberous sclerosis and Rasmussen encephalitis in 1 each. The reasons for the failure of the initial surgery were functional considerations in 8 (35%), incorrect delineation of the epileptogenic zone in 8 (35%), and resection not performed as initially planned in 7 (30%) cases. Final procedures included 8 (35%) intralobar, 8 (35%) multilobar resections, and 7 (30%) hemispherotomies. Following reoperations, 14 (61%) patients were seizure free, 6 (26%) showed significant or worthwhile improvement, and 3 (13%) did not respond to surgery. Six of 8 patients who underwent the first resection before the age of 3 years, 6 of 8 whose first resection was limited by functional considerations, and all 7 with hemispherotomy as the final resection achieved seizure freedom after reoperation.Reoperation is particularly beneficial for selected children with refractory epilepsy associated with cortical dysplasia that did not respond to an initial limited and/or early resection but achieved seizure freedom after extensive procedures. When indicated, reoperation should be performed at the youngest possible age to profit from higher functional plasticity in compensating for neurological deficit.
Gesehen am 14.12.2021